2022
DOI: 10.1177/01461672211067675
|View full text |Cite
|
Sign up to set email alerts
|

“Proof Under Reasonable Doubt”: Ambiguity of the Norm Violation as Boundary Condition of Third-Party Punishment

Abstract: In six studies, we consistently observed costly third-party punishment (3PP) to decrease under ambiguity of the norm violation. Our research suggests that, under ambiguity, some people experience concerns about punishing unfairly. Those with higher (vs. lower) other-oriented justice sensitivity (Observer JS) reduced 3PP more pronouncedly (in Studies 1–3 and 4b, but not replicated in Studies 4–5). Moreover, those who decided to resolve the ambiguity (hence, removing the risk of punishing unfairly) exceeded the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In each condition, it was uncertain for third parties whether the perpetrator was going to counterpunish (CPUN) or whether the algorithm was going to impose additional costs (APUN). While researchers have highlighted the importance of cost uncertainty in explaining punishment behavior 31 , research on punishment behavior under situational uncertainty 32 , and more speci cally, under cost uncertainty 33 , is scarce or inconclusive. The present research showed that the introduction of uncertain additional costs had a substantial detrimental effect on third parties' willingness to punish a norm violation.…”
Section: Discussionmentioning
confidence: 99%
“…In each condition, it was uncertain for third parties whether the perpetrator was going to counterpunish (CPUN) or whether the algorithm was going to impose additional costs (APUN). While researchers have highlighted the importance of cost uncertainty in explaining punishment behavior 31 , research on punishment behavior under situational uncertainty 32 , and more speci cally, under cost uncertainty 33 , is scarce or inconclusive. The present research showed that the introduction of uncertain additional costs had a substantial detrimental effect on third parties' willingness to punish a norm violation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the articles that were excluded during the full-text screening did not meet one or more of the inclusion criteria ( n = 89, see Figure 2). Additionally, we excluded three studies measuring altruistic behavior, using a continuous outcome variable (Friedrichsen et al, 2022; Kajackaite, 2015; Toribio-Flórez et al, 2023). The continuous measures of altruistic behavior do not allow a straightforward categorization of what counts as a selfish/altruistic choice.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies (including Dana et al, 2007), the decision makers can acquire information for free. Other studies have implemented a symbolic cost for information to mimic real-life situations in which information is costly (e.g., Momsen & Ohndorf, 2019;Momsen & Ohndorf, 2020a;Toribio-Flo ´rez et al, 2023). Such costs should make information less attractive (e.g., Leib, 2023;Serra-Garcia & Szech, 2019) and provide participants with an additional justification to remain ignorant and act selfishly.…”
Section: Situational Factorsmentioning
confidence: 99%
“…Regarding the relevance of (i) interpretive processes, research has indicated that subjective uncertainty regarding a norm violation (Greitemeyer et al, 2006; Kemper et al, 2022; Toribio‐Flórez et al, 2023) and low perceived moral severity (Hofmann et al, 2018; Near & Miceli, 1996) might be substantial barriers to intervention. Similarly, (ii) a low sense of own responsibility was found to be related to non‐intervention, as indicated by intervention intentions (Ashburn‐Nardo et al, 2014; Chaurand & Brauer, 2008) and retrospective reports (Greitemeyer et al, 2006, Study 3).…”
Section: Introductionmentioning
confidence: 99%